The introduction of the International Classification of Functioning (ICF) in Education in Portugal - Candeias, Adelinda (2012)
Based on the recent changing of the Portuguese legislation for pupils that experience difficulties in development and learning, screening and assessment, we aim to characterize and discuss the implementation of the ICF in the portuguese educational system. We focus on the challenges to educational assessment and intervention based on the experience of the last threee years in Portugal , with reference to the studies that analyse and discuss such experiences. Our discussion will focus on the implications and requirements derived from the implementation of the CIF in teachers' and others experts' education, in teamwork, and in the process of assessment and intervention to improve inclusive school.